2016
DOI: 10.5603/gp.2016.0042
|View full text |Cite
|
Sign up to set email alerts
|

Power morcellation for women undergoing laparoscopic supracervical hysterectomy — safety of procedure and clinical experience from 426 cases

Abstract: Objectives: Minimally invasive gynaecological surgeries are performed for several malignant and nonmalignant indications. The aim of our study was to evaluate the rate of unexpected malignancies among women who underwent laparoscopical supracervical hysterectomy (LASH) with power morcellation. Material and methods:The retrospective analysis included clinical data of 426 consecutive female patients who underwent LASH with power morcellation due to presumed benign disorders (78.4% -symptomatic uterine fibromas, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…The most frequent occult malignancy was EC, eg. previous Polish study showed the incidence of EC equal to 1:142 [27]. No EC was encountered in our cohort, however 3 cases of AH were confirmed postoperatively.…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…The most frequent occult malignancy was EC, eg. previous Polish study showed the incidence of EC equal to 1:142 [27]. No EC was encountered in our cohort, however 3 cases of AH were confirmed postoperatively.…”
Section: Discussionsupporting
confidence: 43%
“…EC, are considered easy to detect. However, the incidence of undetected morcellated EC may be higher, as was shown in another Polish study [27]. These incidents are a mater of financial compensation to the victims, especially in United States.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…All these patients underwent abdominal reoperations and no histological abnormalities were detected in the extirpated cervix and adnexa. The study concluded that the incidence of unintended endometrial carcinoma in morcellated uteri after LASH was relatively small [14]. However, careful preoperative counseling should be undertaken in order to exclude the possibility of any malignant disease in uteri among women scheduled to power morcellation [14].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of a recent study by Rechberger et al [14] was to evaluate the rate of unexpected malignancies among women who underwent laparoscopic supracervical hysterectomy (LASH) with power morcellation. The retrospective analysis included clinical data of 426 consecutive female patients who underwent LASH with power morcellation due to presumed benign disorders (78.4%-symptomatic uterine fibromas, 12.7%-abnormal uterine bleeding, 8.9%-suspicion of uterine adenomyosis) between January 2011 and December 2015.…”
Section: Discussionmentioning
confidence: 99%